The Interaction of Digital Technologies with the Development of Cognitive and Communication Processes of Adolescents and Young Adults: a Review of Empirical Research - N.Ya. Ageev; Y.A. Tokarchuk; A.M. Tokarchuk; E.V. Gavrilova (Психолого-педагогические исследования)
The article presents an overview of empirical research on the interaction of digital technologies with the development of cognitive and communication processes of adolescents and young adults. The studies are divided into blocks in accordance with the three types of childrens’ activity, such as leisure (including video games), communicative and educational activity – taking the impact of digital technologies into account. Contradictory empirical data are explained by the many limitations that exist for the organization of this type of research. They also do not allow to identify clear causal relationships between the use of digital technologies by adolescents and young adults and the development of their cognitive and communication skills. The analysis of scientific results, studies led to the conclusion that digitalization qualitatively changes development of cognitive and communication processes of adolescents and young adults.